2006
DOI: 10.1158/1078-0432.ccr-06-0417
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Serum Caveolin-1 as a Prognostic Marker for Recurrence in a Radical Prostatectomy Cohort

Abstract: Purpose: Up-regulation of caveolin-1 (cav-1) is associated with virulent prostate cancer, and serum cav-1levels are elevated in prostate cancer patients but not in benign prostatic hyperplasia. In this study, we evaluated the potential of high preoperative serum cav-1 levels to predict biochemical progression of prostate cancer. The value of the combined preoperative markers, prostate-specific antigen (PSA), biopsy Gleason score, and serum cav-1for predicting biochemical recurrence was also investigated. Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 9 publications
4
60
1
1
Order By: Relevance
“…When focused on prostate cancer, elevated caveolin-1 expression was observed in tumour tissue and in mice when compared to non-tumour tissue (64)(65)(66). According to Thompson et al, caveolin-1 is also elevated in the serum of patients with localized tumours compared to healthy controls and patients with benign prostatic hyperplasia (67,68). These findings are inconsistent with ours; we found no significant difference between controls and cancers.…”
Section: Discussioncontrasting
confidence: 99%
“…When focused on prostate cancer, elevated caveolin-1 expression was observed in tumour tissue and in mice when compared to non-tumour tissue (64)(65)(66). According to Thompson et al, caveolin-1 is also elevated in the serum of patients with localized tumours compared to healthy controls and patients with benign prostatic hyperplasia (67,68). These findings are inconsistent with ours; we found no significant difference between controls and cancers.…”
Section: Discussioncontrasting
confidence: 99%
“…Tahir et al [22] found higher levels of secreted Caveolin-1 in patients with prostate cancer compared with those with BPH or no evidence of prostate neoplasm. Furthermore, in a cohort of 414 patients with prostate cancer treated with RP, patients with higher preoperative Caveolin-1 levels had a 2.6-fold higher risk of BCR after RP than those with low levels [23]. In addition to its promising role as a biomarker, Caveolin-1 is being evaluated as a target for therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Caveolin-1, a regulatory molecule involved in cell to cell signal transduction, has been shown to be overexpressed in advanced CaP and may have prognostic value as a serum marker. 122 E-cadherin, b-catenin and matrix metalloproteinases are also involved in altered cell adhesion and cellular migration and appear to be promising biological markers associated with disease aggressiveness. 123,124 Other potential protein biomarkers include inhibitors of metalloproteinases, 125 hepatocyte growth factor, 126 macrophage migration inhibitory factor, 127 progastrin-releasing peptide 128 and 50.8 kDa protein.…”
Section: Other Markersmentioning
confidence: 99%